Knowledge and perceptions of secondary school adolescents on causes and prevention of mental illness at Katoto Day Secondary School - Kumwenda, M. Mtalimanja Gad (Kamuzu University of Health Sciences, 2022)
Adolescents' mental health is influenced by many factors which are usually overlooked by adolescents themselves and policy makers. These factors include HIV&AIDS, poverty, Orphan hood, unstable families, excessive alcohol consumption, cannabis, anxiety and stress. Therefore, this descriptive qualitative study sought to describe knowledge and perception of adolescents on causes and prevention of mental illness. The study was aimed at identifying gaps in adolescents' knowledge and perception on causes and prevention of mental illness so that appropriate interventions can be developed for them. The knowledge will also be used to identify problem areas on which nurses ought to emphasize when giving health education to adolescents on mental health. The study was conducted at Katoto secondary school, the researcher chose this site because it is close to Mzuzu city and felt that this may predispose these adolescents to mental illness. The study used descriptive qualitative design. A purposive sample of ten male and ten female students was used. Data was collected using interview guide comprising of open-ended and closed-ended questions and was analyzed manually using content analysis. Consent forms were signed by participants after explaining to potential participants what the study was all about such as the purpose, benefits, risks and significance so that potential participants make an informed decision whether to participate or not. Confidentiality and privacy was ensured by using codes instead of students' names and interviews were conducted in a private room. Participants were also allowed to make their own decisions and choices throughout the study process such as withdrawing from participation in the study without reprisal. The results have shown that adolescents do not have adequate knowledge about causes and prevention of mental illness. Beliefs and myths have also shown that they influence adolescents' knowledge and perceptions about mental illness. The researcher intends to disseminate study findings to KCN library, Katoto secondary school and mental hospitals.